2019
DOI: 10.1093/jmammal/gyz079
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, precision, and error in age estimation of Florida manatees using growth layer groups in earbones

Abstract: Ages of Florida manatees (Trichechus manatus latirostris) can be estimated by counting annual growth layer groups (GLGs) in the periotic dome portion of the tympanoperiotic complex of their earbones. The Florida Fish and Wildlife Conservation Commission manages an archive of more than 8,700 Florida manatee earbones collected from salvaged carcasses from 1989 to 2017. Our goal was to comprehensively evaluate techniques used to estimate age, given this large sample size and changes to processing protocols and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 60 publications
4
16
0
Order By: Relevance
“…Uncertainty surrounds estimated ages of animals. For example, previous research indicated that counts of annual GLGs in the periotic domes of the tympanoperiotic complexes of manatees became less accurate for older animals, especially those over 15 years old (Lonati et al, 2019). However, the same study documented little to no resorption of annual GLGs for specimens ≤10 years old; therefore, we are confident in identifications of younger animals.…”
Section: Parametermentioning
confidence: 71%
“…Uncertainty surrounds estimated ages of animals. For example, previous research indicated that counts of annual GLGs in the periotic domes of the tympanoperiotic complexes of manatees became less accurate for older animals, especially those over 15 years old (Lonati et al, 2019). However, the same study documented little to no resorption of annual GLGs for specimens ≤10 years old; therefore, we are confident in identifications of younger animals.…”
Section: Parametermentioning
confidence: 71%
“…Adult females were consistently longer than males in the present study (Figs. S4 & S5), and there is evidence that males' growth rate slows relative to females' after animals reach approximately 300 cm in total length (Schwarz & Runge 2009, Lonati et al 2019: particularly their Fig. 7).…”
Section: Sex Differences In Scarringmentioning
confidence: 93%
“…When examining sub adults for trends across the 10 yr period of this study (Models S-P and S-N), a general increase was observed. Lonati et al (2019) found that animals in the subadult size category had an approximate age range of 2−10 yr based on counts of growth layers in earbones, although most were 2−6 yr old. There may be too much age variation to rely on subadult lengths for this analysis.…”
Section: Scar Accumulation Over Timementioning
confidence: 99%
“…For example, we fixed to 0 the probability of recording age 0 and age 1 manatees as adults (Appendix S4). Alternatively, using data such as actual size measurements or growth layer counts (Lonati et al 2019) as imperfect indicators of age can also be considered for extending our model, in which observation events are continuous rather than discrete and assumed to be a parametric function of age (also see Appendix S2…”
Section: Accepted Articlementioning
confidence: 99%